Compound Danshen Dripping Pill Pretreatment to Prevent Contrast-Induced Nephropathy in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention. (16th October 2014) - Yang, Rong; Chang, Liang; Guo, Bing-yan; Wang, Yan-wei; Wang, Ya-ling; Jin, Xin; Liu, Su-yun; Li, Yong-jun
Abstract : Background . Contrast-induced nephropathy (CIN) limits the outcome of percutaneous coronary intervention (PCI). Objective . To investigate whether pretreatment with Compound Danshen Dripping Pills (CDDP) will decrease the incidence of CIN after PCI. Methods . A total of 229 patients with acute coronary syndrome (ACS) undergoing PCI were divided into the control group (n = 114 ) and the CDDP (containing salvia miltiorrhiza and sanqi) group (n = 115 ; given 20 CDDP pills, three times daily before PCI). Serum creatinine, creatinine clearance (CrCl), high-sensitivity C-reactive protein (hsCRP), P-selectin, and intercellular adhesion molecule-1 (ICAM-1) were measured at admission and 24 and 48 h after PCI. Results . CrCl decreased after PCI but recovered after 48 h. In the CDDP group, CrCl recovered more rapidly (P < 0.05 ). The procedure increased the hsCRP, P-selectin, and ICAM-1 levels, but these levels were less in the CDDP group (P < 0.05 ). Conclusions . Pretreatment with CDDP can decrease the occurrence of CIN in patients undergoing PCI, suggesting that the early use of CDDP is an appropriate adjuvant pharmacological therapy before PCI.